Comparison of antimicrobial effect of Tricresol formalin and 5.25% Sodium Hypochlorite on the Enterococcus faecalis - Fatemeh Mokhtari; Hengame Zandi; Asghar Nafez (Tehran University of Medical Sciences, 2016)
Background and Aims: The presence of microbes inside the canal is the main reason for post-treatment infection. Therefore, the maintenance of the disinfection obtained during the treatment is imperative. The aim of this study was to compare the antimicrobial effect of Tricresol formalin and 5.25% Sodium hypochlorite on the Enterococcus faecalis. Materials and Methods: In this study 66 human single-rooted extracted teeth were used. After access cavity and root canal preparation, the teeth were sterilized in autoclave, and then contaminated with Enterococcus faecalis suspension and incubated at 37°C for 7 days. Then, they were randomly divided into three groups of 20: In group 1, Tricresol formalin was used as intracanal medicament. In group 2, 5.25% Sodium hypochlorite and in group 3 (control group), normal saline were used as irrigants. 7 days after incubation at 37°C, the microbiological sampling was performed. For this purpose, dentinal shaves were collected from the root canals and cultured in Tryptic Soy Broth, and the number of Colony-Forming Unit (CFU) was counted. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests. Results: A significant reduction of CFU was observed in the Tricresol formalin and Sodium hypochlorite groups compared to the control group (P<0.001). No significant difference was reported between Tricresol formalin and Sodium hypochlorite groups (P=0.69). Conclusion: The present study showed that the antimicrobial effect of Tricresol formalin was comparable with 5.25% Sodium hypochlorite on the Enterococcus faecalis.